A Software System for Data Analysis in Automated DNA Sequencing - Giddings, Michael C.; Severin, Jessica; Westphall, Michael; Wu, Jiazhen; Smith, Lloyd M. (Genome Research, 1998)
Software for gel image analysis and base-calling in fluorescence-based sequencing consisting of two primary programs, BaseFinder and GelImager, is described. BaseFinder is a framework for trace processing, analysis, and base-calling. BaseFinder is highly extensible, allowing the addition of trace analysis and processing modules without recompilation. Powerful scripting capabilities combined with modularity and multilane handling allow the user to customize BaseFinder to virtually any type of trace processing. We have developed an extensive set of data processing and analysis modules for use with the program in fluorescence-based sequencing. GelImager is a framework for gel image manipulation. It can be used for gel visualization, lane retracking, and as a front end to the Washington University Getlanes program. The programs were designed using a cross-platform development environment, currently allowing them to run in Windows NT, Windows 95, Openstep/Mach, and Rhapsody. Work is ongoing to deploy the software on additional platforms, including Solaris, Linux, and MacOS. This software has been thoroughly tested and debugged in the analysis of >2 million bp of raw sequence data from human chromosome 19 region q13. Overall sequencing accuracy was measured using a significant subset of these data, consisting of ∼600 sequences, by comparing the individual shotgun sequences against the final assembled contigs. Also, results are reported from experiments that analyzed the accuracy of the software and two other well-known base-calling programs for sequencing the M13mp18 vector sequence.[The sequence data described in this paper have been submitted to the GenBank data library under accession no. AF025422]